1978
DOI: 10.1002/ijch.197800011
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Nucleophilic Displacement of Fluorine

Abstract: Intramolecular nucleophilic displacement in organic fluorine compounds takes place if a fluorine atom is located in the molecule at such a distance from a nucleophilic functional group as to allow cyclization to three-membered rings (in aliphatic compounds only), five-membered rings, six-membered rings, and, exceptionally, seven-and polymembered rings (in aromatic series only). The nucleophilic functions can be hydroxyl groups of alcohols, enols, phenols and carboxylic acids, sulfhydryl groups, primary or seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Intramolecular S N 2 reaction of alkyl fluorides, however, did not attract much attention for a long time probably due to the “common sense” that the C−F bond is highly stable. In many early publications, some unexpected intramolecular nucleophilic substitution reactions of the C−F bond were observed, but most of these discoveries were considered as undesirable and sometimes even as side reactions . Although some early examples of these C−F cleavage reactions were summarized by Hudlickly, there is still a lack of detailed and systematic study of intramolecular nucleophilic substitution of alkyl fluorides with different nucleophiles to determine both the scope and chemical yields of the reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intramolecular S N 2 reaction of alkyl fluorides, however, did not attract much attention for a long time probably due to the “common sense” that the C−F bond is highly stable. In many early publications, some unexpected intramolecular nucleophilic substitution reactions of the C−F bond were observed, but most of these discoveries were considered as undesirable and sometimes even as side reactions . Although some early examples of these C−F cleavage reactions were summarized by Hudlickly, there is still a lack of detailed and systematic study of intramolecular nucleophilic substitution of alkyl fluorides with different nucleophiles to determine both the scope and chemical yields of the reactions.…”
mentioning
confidence: 99%
“…In many early publications, some unexpected intramolecular nucleophilic substitution reactions of the C-F bond were observed, but most of these discoveries were considered as undesirable and sometimes even as side reactions. 10 Although some early examples of these C-F cleavage reactions were summarized by Hudlickly, 10 there is still a lack of detailed and systematic study of intramolecular nucleophilic substitution of alkyl fluorides with different nucleophiles to determine both the scope and chemical yields of the reactions. In this Note, we wish to disclose our recent study on this topic, which provides new insights into the intramolecular nucleophilic substitutions of primary and secondary alkyl fluorides with different nucleophiles.…”
mentioning
confidence: 99%
“…Thus, compared to C−Br and C−I bonds, the participation of C−F bonds in S N 2 pathways is far less common. However, select examples have demonstrated that intramolecular systems can enable this pathway, where the incoming nucleophile originates from a deprotonated alcohol [39–41] . In addition to the intramolecular formation of 5 or 6‐membered rings, [40] 3‐membered rings (epoxides) can also form (Figure 1a, ii) [25,42,43] .…”
Section: Introductionmentioning
confidence: 99%
“…However, select examples have demonstrated that intramolecular systems can enable this pathway, where the incoming nucleophile originates from a deprotonated alcohol. [39][40][41] In addition to the intramolecular formation of 5 or 6-membered rings, [40] 3-membered rings (epoxides) can also form (Figure 1a, ii). [25,42,43] For example, ethylene oxide was reported to form from 2-fluoroethanol under basic conditions, [42] and a defluorinated epoxide was reported as a side product in 10 % yield from the reaction of benzophenone with a LiCH 2 F. [41] To the best of our knowledge, there are no reports of similar reactions from polyfluorinated alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of tetrahydrofuran 2 from fluoroalcohol intermediates VI (Scheme ) was unexpected, as such nucleophilic substitution at a nonactivated C­(sp 3 )-F position has rarely been reported in the literature. , Further modification of the reaction conditions B led to the development of an alternative stepwise protocol for the synthesis of fluoroalcohols as the major products (Scheme ). A fluorohydroxylation step was first implemented by treating alkenes 1 with Selectfluor in the presence of water (5 equiv) in MeNO 2 .…”
mentioning
confidence: 99%